The value co-creation journey: a longitudinal process unfolding in a network through collaboration. Issue 13 (28th November 2022) - Perna, Andrea; O'Toole, Thomas; Baraldi, Enrico; Gregori, Gian Luca
Abstract : Purpose: This study aims to develop our understanding of the value co-creation process in business networks. This study identifies four key sub-processes that characterize the value co-creation journey as it unfolds across an inter-organizational network. These four sub-processes are opportunity co-creation, solution co-creation, complementary co-creation and activated co-creation. Design/methodology/approach: Reflecting the exploratory nature of this research, the methodology relies on an in-depth case study, which is analyzed through the lens of the resource interaction occurring within the specific business relationships and collaborative episodes that affected the nine-year long development of Deko, a new architectural lighting solution. Findings: The main contribution of the paper is identifying the sub-processes comprising the value co-creation journey of a technology development solution based on resource combining, re-combining and un-combining across a business network. That value co-creation occurs through a time-consuming journey requiring multiple episodes of collaboration can also inspire the practice of handling this process for instance for a small business such as the one featured in this case study. Originality/value: This paper highlights that the value co-creation journey process has the potential to frame the unfolding of collaboration in practice for a small business.